2015
DOI: 10.1080/09640568.2015.1090961
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variation in habitat survey data: investigating the consequences for professional practice

Abstract: Environmental assessments and land use planning require reliable information on the botanical composition and distribution of habitats. There have been numerous academic studies of inter-observer variation in species-inventory and habitat mapping, but studies addressing the prevalence of inter-observer variation and consequences of poor quality data in professional practice are lacking. This paper addresses these questions via a questionnaire survey of environmental professionals using the standard Phase 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This means that some field workers are not successful in correctly mapping specific features. This agrees with studies that explored the accuracy of vegetation mapping, which found that individual skills affected the values of MCO error rates [34,35,56]. Moreover, our results indicated that in some landscapes, individual characteristics may have had a bigger effect on mapping quality than in other landscapes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This means that some field workers are not successful in correctly mapping specific features. This agrees with studies that explored the accuracy of vegetation mapping, which found that individual skills affected the values of MCO error rates [34,35,56]. Moreover, our results indicated that in some landscapes, individual characteristics may have had a bigger effect on mapping quality than in other landscapes.…”
Section: Discussionsupporting
confidence: 82%
“…For example, in the built-up-diverse landscapes, the variation of error rates and overall error rates were lower than in closed-complex and open-simple landscapes, which suggests that built-up areas were easier to map than natural areas. In contrast, different vegetation communities that are similar in species composition and appearance can be easily confused in fieldwork in natural areas [35,56].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to take potential error in land-cover maps into account may have unfortunate consequences for practical management, such as giving priority to low-value sites while sites of higher conservation value are lost. In a survey among British environmental professionals (Cherrill 2016), about one third of the respondents reported experience with net loss of biodiversity due to errors in assignment of land-cover types. In many more cases, mistakes incurred additional costs for the respondents' firms or clients.…”
Section: Implications For Nin and Land-cover Mappingmentioning
confidence: 99%
“…the process of drawing a multitude of non-overlapping unique land-cover polygons covering the entire extent of the intended map. Cherrill andMcClean (1995, 1999a) indicated that very different placement of boundaries in compared maps are likely due to differences in land-cover-type assignment rather than differences in the observers' perception of transitions between types. They applied buffers around polygon boundaries and compared only the 'core areas' of polygons to separate the effect of type assignment.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate management depends on correct assignment of sites to types (Cherrill & McClean, ) and consistent delineation of polygons (Hunter, ). Net loss of biodiversity may result from the use of land‐cover maps that fail to meet these demands for quality (Cherrill, ). One of the most important obstacles to consistency in field‐based land‐cover maps is among‐observer behavioral differences, i.e.…”
Section: Introductionmentioning
confidence: 99%